On the discursive construction of social entrepreneurship in pitch situations: the intertextual reproduction of business and social discourse by presenters and their audience - Kreutzer, Karin (Journal of business ethics, 2022)
This study explores the discourse of social entrepreneurs and their audiences in pitch situations. Adopting a practice perspective on social entrepreneurship, we videotaped 49 pitches by social entrepreneurs at five different events in two incubators in Germany and Switzerland. Our analysis of the start-ups’ pitches and the audience’s questions and comments as well as of interview data elucidates the nuances of social and business discourse that social entrepreneurs and their audiences draw upon. Our analysis shows how many social entrepreneurs mobilize a discursive repertoire that is familiar to their business-oriented audience while others predominantly draw on a social discourse. We identify separating, mixing, and combining as key strategies that allow social entrepreneurs to dance between the two. We discuss how the intertextual reproduction of concepts, objects, and subject positions contains both enabling and constraining elements, which results in an ethical dilemma for social entrepreneurs: Should they re-package their social impact story in a business discourse to connect with their audience?